The Silver chair - Lewis, C. S. (Clive Staples), 1898-1963.; Baynes, Pauline; HarperCollins Children's Books (London : HarperCollins Children's Books, 1998)
Two English children undergo hair-raising adventures as they go on a search and rescue mission for the missing Prince Rilian, who is held captive in the underground kingdom of the Emerald Witch.
Keywords: Narnia (Imaginary place) -- Fiction; Fantastic fiction